Analisis Kesalahan Mahasiswa dalam Memecahan Masalah Nonrutin pada Materi Fungsi Kuadrat - Rahmat Syam; Awi Dassa; Siti Khodidah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2020)
This study was a descriptive research by using qualitative approach that aimed to describe the errors made by students in quadratic function real life problems based on basic mathematical objects (facts, principles, concepts, and operation). The data coll